A SYSTEMIC FRAMEWORK FOR IMPLEMENTATION OF TQM PROGRAMMES - Mwaluko, G S; Mjema, E A. M (Tanzania Journal of Engineering and Technology, 2017)
The purpose of this paper is to present a systemic framework for implementation of TQM program in a manufacturing organisation that produces motor vehicle components in Port Elizabeth - South Africa. The approach used included conceptualisation of the systemic framework and then involvement of the stakeholders in adding scenarios to be considered in the design and implementing the framework in the real field. The findings obtained during the implementation of the systemic framework established that reduction of scrap rate, reduction of production costs, reduction of cycle time and employee motivation could be achieved through the implementation of a Systemic Framework for the TQM programme. The TQM team was satisfied that the implementation of TQM programme using the systemic framework was relevant in their particular situation. The developed systemic framework for implementation of TQM was tested in a company that manufactures motor vehicle components. The experience gained shows that the framework has a big potential for successful implementation of TQM. The developed systemic framework has a holistic approach in implementation of TQM; in that case it can be used to guide the design and implementation of successful TQM programmes. The developed systemic framework is a holistic approach, which took on board all four basic characteristics that portray an organisation. Organisations are portrayed by four interrelated characteristics namely, organisational processes, organisational design, organisational culture and organisational politics. For a successful implementation the TQM intervention should take into consideration these four characteristics.